Neoliberarismo, privatização de gestão e subjetividade: um estudo sobre o cotidiano dos trabalhadores da Escelsa. - Ferrari, André Luiz Sant´Ana (2005)
The proposal of the present work was analyze the impact of the policy of human management of Escelsa (Centrais Elétricas do Espírito Santo S. A.) on the quotidian of the workers. The company studied sells electric energy for the state of Espírito Santo an